Examining the Gender Leadership Gap : A Case Study of Corporate Dynamics at a Big Four Company - Dubničková, Terézia; Blažková, Hana; Nencková, Lucie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The thesis examines the gender leadership gap within one of the Big Four accounting firms, focusing on systemic barriers and enablers that impact women’s advancement into leadership roles. The first part presents an overview of the current gender equity landscape in European Union and Czech Republic, highlighting significant disparities in women's representation in leadership positions, despite various initiatives aimed at promoting gender diversity. The study is based on identifying critical obstacles that women face, such as implicit biases favouring male leadership traits, limited access to mentorship, and societal expectations regarding caregiving responsibilities. To gather insights, the research employs nine semi-structured interviews with employees within the Company, aiming to understand their experiences and perceptions regarding gender diversity policies. Key findings reveal that while the firm has implemented several measures to support women's career advancement, such as mentoring programs and flexible work arrangements, the overall representation of women in senior leadership roles remains disproportionally low. Eventually, the thesis seeks to provide actionable recommendations for enhancing gender equity within the Company, ultimately contributing insights to both academic literature and practical applications in corporate settings in Czech Republic.
Vedoucí práce: Hana Blažková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses